Roda com arte : aprendizagem dialógica em comunidades de aprendizagem - Marigo, Adriana Fernandes Coimbra (Universidade Federal de São Carlos, 2009)
It is presented in this research the preparation and consolidation of a project involving artistic works with children who study in a school in the outskirt of São Carlos town, where the proposal of Learning Communities is consolidated. From this suggestion, the scholar educational practices are based on the contributions of Jünger Habermas Communicative Action Theory, Paulo Freire s Dialogic Action Theory and the concept of dialogic learning developed by CREA/ES, besides others from authors who have been worried with social transformations and with the overcoming of educational disparity, having as an aim the insertion in the information society. The investigation had its establishment in the reflection that the interpersonal conflicts are pointed out by the academic literature as one of the main difficulties related to educational and didactic actions. However, some of the studies deriving from the philosophy, psychology and sociology in their interfaces with education has also aimed that school and social learning are not susceptible of concretization out of human interactions. Placed in the didactic and educational field, the examination started from a larger focus about the interactions in the school context, specifying gradually the scholar process and the conception given to the activity about the artistic works called Roda com Arte Project. Having as an objective basis, the dialog was adopted with people from the school to achieve the general purpose in order to understand the educational procedures that are manifested in reflective activities about the artistic works in the dialogic learning perspective. The investigation had the participation of six people, being three children, two teachers and one pedagogical coordinator, who acted in the community studied. In agreement with the principles of the learning communities supervisors, it was used the proceedings of critical communicative methodology to collect and analyze the data, having as the fundamental support the intersubjectivity and reflective categories. In the end of this survey, the main results found were: the learning capability of children from lower social classes starting with interdisciplinary work with the school contents and the knowledge involvement, as well as the experiences proceeding from the school context, as out of it. The potentiality of artistic work and the use of imagination to the teaching in addition to the reinforcement of the scholar and social learning intending to express thoughts and feelings, moreover the need of permanent teaching formation in theories and practices, which allow the knowledge actualization and a supportive teaching concerned with the social transformations. In general, the contributions were evidenced to the Learning Communities proposal, to the investigations in schools and with children, furthermore to the educational and didactic field.
Keywords: Aprendizagem; Didática; Diálogo; Crianças; Escola; Interação; CIENCIAS HUMANAS::EDUCACAO